Legitymizacja systemu instytucjonalnego Unii Europejskiej jako organizacji międzynarodowej sui generis (Politeja, 2016)
Legitimization of the institutional system of the European Union as an international organization sui generisThe legitimacy of political power is one of the most important theoretical and research problems related to power as a social phenomenon and the very important issue of practice of its exercise, the functioning of the political institutions, political systems etc. Both scientific reflection and empirical research on legitimacy of political power are devoted mainly to this issue in relation to the state and its institutions. The purpose of the study is to present the issue of legitimacy of the European Union’s institutional system as a specific, sui generis, international organization. In the first part of the article the problem of “democracy deficit” and “legitimacy deficit” in the functioning of the EU and its institutions is synthetically showed. In the next part it has been identified the specific features of the EU as an international organization and its institutional system which have the key importance to the question of legitimacy. The last section contains conclusions, that is consequences resulting from the nature of the EU and its institutional system in the context of the problem of legitimacy.